The Impact of YouTube as an Interactive Social Studies Learning Platform for 7th Grade Students at Junior High School - Mawarni, Ersa Wahyu; Sulistyarini, Sulistyarini; Karolina, Venny; Ulfah, Maria; Barella, Yusawinur (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research regarding the use of YouTube learning media in ssocial studies subjects aims to determine its influence or impact on students as seen from the learning outcomes scores in class VII at SMP Negeri 1 Sungai Pinyuh. This research was conducted using a pre-experimental method with a one-group pretest-posttest design. The sample used comprises students from the class with the lowest average formative scores. The conclusive findings of the research suggest that using YouTube as an educational tool in the classroom positively impacts students' academic achievements. This is evident from the student's learning outcomes after the treatment, where most students showed significant improvement: 50% (N=16) reached the "Developing as Expected" category, and 22% (N=7) reached the "Highly Developing" category. Furthermore, only a few students fell into the "Not Yet Developing" category after the treatment, at 6% (N=2). This result is also supported by the effect size test, which is 2.30. This suggests that using YouTube as a learning medium significantly influences the learning outcomes of 7th-grade social studies students at SMP Negeri 1 Sungai Pinyuh, specifically on the topic “Mengenal Lokasi Tempat Tinggal."